Difference Model Problem Based Learning (PBL) and Discovery Learning (Dl) on Results Study and Motivation Study Students At Bonding Materials Chemistry in Senior High School - Situmeang, Amanda Zefanya; Ginting, Elfrida (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research aims to: (1) determine the differences in student learning outcomes taught using the Problem Based Learning (PBL) and Discovery Learning (DL) models on chemical bonding material. (2) determine the differences in students' learning motivation who are taught using the Problem Based Learning (PBL) and Discovery Learning (DL) models on chemical bond material. (3) there is a correlation between motivation and learning outcomes of students who are taught using the Problem Based Learning (PBL) and Discovery Learning (DL) models on chemical bond material. This research was conducted at SMAN 11 Medan with the samples studied were X-3 and X-7. The instrument used is a test instrument in the form of multiple choice questions with 20 validated questions and a non-test in the form of a learning motivation questionnaire. Data analysis techniques are carried out by: Data normality test, data homogeneity test, hypothesis test, and correlation test. The results obtained: (1) There are differences in student learning outcomes taught using the Problem Based Learning and Discovery Learning models on chemical bonding material. The average student learning outcomes in experimental class I using Problem Based Learning was 74.8. Meanwhile, the average learning outcome for experimental class II using the Discovery Learning model was 79.6. (2) There were differences in the learning motivation of students who were taught using the Problem Based Learning and Discovery Learning models on chemical bond material. Meanwhile, the average learning motivation of students in experimental class I using Problem Based Learning is 67.6. Meanwhile, the average learning motivation in experimental class II which was taught using the Discovery learning model was 72.5. (3) There is a correlation between students and learning outcomes taught using the Problem Based Learning and Discovery Learning models on chemical bond material with a positive correlation value. In experimental class I obtained Sig. = 0.00 with Pearson Correlation = 0.795 and experimental class II Sig. = 0.000 with Pearson Correlation = 0.879.